Structural changes in vortex vein ampullae in eyes with pachychoroid-spectrum disorder - Ryoh Funatsu; Hiroto Terasaki; Shozo Sonoda; Naohisa Mihara; Mariko Hirokawa; Yasushi Tanabe; Hideki Shiihara; Taiji Sakamoto (Scientific Reports)
Abstract The purpose of this study is to identify the characteristics of vortex vein ampullae in pachychoroid-spectrum disorders. This case-control study evaluated vortex vein ampullae using Optos Silverstone, an imaging device combining ultra-widefield scanning laser fundus imaging with swept-source optical coherence tomography. Consecutive patients with pachychoroid-spectrum disorders and controls who visited Kagoshima university hospital between January 2022 and December 2023 and underwent vortex vein ampullae evaluations. We compared morphological parameters of supratemporal and infratemporal vortex vein ampullae between eyes with pachychoroid-spectrum disorders and control subjects. We included 40 patients (46 eyes) with pachychoroid-spectrum disorders, and 14 healthy controls (15 eyes). We observed no significant differences in any supratemporal vortex vein ampullae morphological parameters (P ≥ 0.487 for all comparisons). In infratemporal vortex vein ampullae, eyes with pachychoroid-spectrum disorders showed significantly larger mean luminal volume (6.9 × 106 ± 1.8 × 106 pixels vs. 4.7 × 106 ± 1.5 × 106 pixels, P < 0.001) and greater mean vessel diameter (P = 0.040) compared to controls, with no significant differences in luminal proportions (P = 0.353). After adjusting for potential confounders, the pachychoroid-spectrum disorders group still demonstrated significantly larger infratemporal vortex vein ampullae luminal volume and mean vessel diameter compared to controls (P ≤ 0.011 for both analyses). Enlargement of lumen and stroma was observed exclusively in the infratemporal vortex vein ampullae in eyes with pachychoroid-spectrum disorders. Impaired choroidal drainage alone may not fully account for the observed vortex vein ampullae alterations.